2009
DOI: 10.1176/appi.ajp.2009.08101542
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene (SLC6A4) Promoter Polymorphisms and the Susceptibility to Posttraumatic Stress Disorder in the General Population

Abstract: An additive gene-environment interaction with the high expression L(A) allele of 5-HTTLPR and frequent trauma in PTSD was found. The attributable proportion indicated that more than 60% of all L(A) allele carriers who were exposed to three or more traumas developed PTSD as a result of an interaction between genotype and exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
97
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 36 publications
9
97
0
2
Order By: Relevance
“…The S allele is also positively correlated with post-traumatic stress disorder incidence rate (Kolassa et al, 2010). The L allele may be a protective factor and can reduce the incidence of depression (Grabe et al, 2009). The LL genotype may also increase vascular tension during the stressful event, which may cause ischemia, and is associated with the incidence of vascular events (Brummett et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The S allele is also positively correlated with post-traumatic stress disorder incidence rate (Kolassa et al, 2010). The L allele may be a protective factor and can reduce the incidence of depression (Grabe et al, 2009). The LL genotype may also increase vascular tension during the stressful event, which may cause ischemia, and is associated with the incidence of vascular events (Brummett et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The FS model remains useful in researching individual differences in recovery from traumatic fear, modelling the variation in human susceptibility to PTSD [45] . Other risk factors such as variation in 5-HTTLPR in humans, that affects the prevalence of several anxiety disorders including PTSD, can be assessed in this model as well [46][47][48] . 5-HTT knockout rats, displaying increased freezing and impaired fear extinction [49][50][51] or fear extinction recall [52][53][54] , have been used as model for the more PTSD-susceptible 5-HTTLPR genotype.…”
Section: Yehuda and Antelman's Criteria For Rationally Evaluating Ptsmentioning
confidence: 99%
“…7 Further, we were interested in gender effects, in the effect of an additional functional A/G-polymorphism (rs25531) within the promoter region and in the identification of the risk allele, as some studies found the L-allele to be associated with the risk for depression. 8,9 The 5-HTTLPR and rs25531 polymorphisms were genotyped according to Grabe et al 10 and identical statistical methods and definitions of stressors and outcomes were applied as in the initial report. 5 Besides unemployment as a putative stressor, the interview-rated number of chronic diseases (myocardial infarction, stroke, diabetes, kidney disease, chronic bronchitis, arthritis and degenerative diseases of the joints and spine, osteoporosis, peptic ulcer, pancreatitis, gastrointestinal bleedings, migraine, thyroid disease, cancer, multiple sclerosis, and Parkinson's disease) was taken as another stressor.…”
mentioning
confidence: 99%
“…Infact, we have recently shown the association between the L allele and susceptibility to PTSD. 10 Many of the chronic diseases assessed can have acute manifestations or exacerbations that may qualify the criteria of traumatization.…”
mentioning
confidence: 99%